Individual and joint effects of metformin and statins on mortality among patients with high‐risk prostate cancer. (8th February 2020) - Tan, Xiang‐Lin; E, Jian‐Yu; Lin, Yong; Rebbeck, Timothy R.; Lu, Shou‐En; Shang, Mingyi; Kelly, William K.; D'Amico, Anthony; Stein, Mark N.; Zhang, Lanjing; Jang, Thomas L.; Kim, Isaac Yi; et al.
Abstract: Background: Pre‐clinical studies suggest that metformin and statins may delay prostate cancer (PCa) metastases; however, data in humans are limited. To the best of our knowledge, this is the first human study aimed to quantify the individual and joint effects of statin and metformin use among patients with high‐risk PCa. Methods: This population‐based retrospective cohort study identified patients from the Surveillance, Epidemiology, and End Results (SEER)‐Medicare linked database. Exposure to metformin and statins was ascertained from Medicare Prescription Drug Event files. The association with all‐cause and PCa mortality were evaluated using Cox proportional hazard model with competing causes of death, where propensity scores were used to adjusted imbalances in covariates across groups. Results: Based on 12 700 patients with high‐risk PCa, statin alone or in combination with metformin was significantly associated with reduced all‐cause mortality (Hazard Ratio [HR]: 0.89; 95% Confidence Interval [CI]: 0.83, 0.96; and HR: 0.75; 95% CI, 0.67‐0.83, respectively) and PCa mortality (HR, 0.80; 95% CI: 0.69, 0.92) and 0.64; 95% CI, d 0.51‐0.81, respectively. The effects were more pronounced in post‐diagnostic users: combination use of metformin/statins was associated with a 32% reduction in all‐cause mortality (95% CI, 0.57‐0.80), and 54% reduction in PCa mortality (95% CI, 0.30‐0.69). No significant association of metformin alone was observed with either all‐cause mortality or PCa mortality. Conclusions: Statin use alone or in combination with metformin was associated with lower all‐cause and PCa mortality among high‐risk patients, particularly in post‐diagnostic settings; further studies are warranted. Abstract : In this population‐based cohort study of 12 700 high‐risk prostate cancer patients, statin use alone or combined with metformin was significantly associated with lower all‐cause mortality, particularly in post‐diagnostic settings. Randomized clinical trials are warranted to confirm these findings.